2020
DOI: 10.3390/ma13214885
|View full text |Cite
|
Sign up to set email alerts
|

Ferrierite and Its Delaminated Forms Modified with Copper as Effective Catalysts for NH3-SCO Process

Abstract: Ferrierites and their delaminated forms (ITQ-6), containing aluminum or titanium in the zeolite framework, were synthetized and modified with copper by an ion-exchange method. The obtained samples were characterized with respect to their chemical composition (ICP-OES), structure (XRD, UV-Vis DRS), textural parameters (N2-sorption), surface acidity (NH3-TPD), form and reducibility of deposited copper species (UV-Vis DRS and H2-TPR). Ferrierites and delaminated ITQ-6 zeolites modified with copper were studied as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…It was shown that the presence of aluminum or titanium in the zeolite framework influenced the form and aggregation of deposited copper species. In the case of Ti-zeolites, a significant contribution of aggregated copper species was identified, in contrast to Al-zeolites with higher contribution of the highly dispersed forms of copper [9]. This is not surprising, considering the dominant role of the ion exchange mechanism of copper deposition in Al-zeolites, as well as the much more complex mechanisms involved for Ti-zeolites.…”
Section: Selective Catalytic Oxidation Of Ammonia (Nh 3 -Sco)mentioning
confidence: 89%
See 4 more Smart Citations
“…It was shown that the presence of aluminum or titanium in the zeolite framework influenced the form and aggregation of deposited copper species. In the case of Ti-zeolites, a significant contribution of aggregated copper species was identified, in contrast to Al-zeolites with higher contribution of the highly dispersed forms of copper [9]. This is not surprising, considering the dominant role of the ion exchange mechanism of copper deposition in Al-zeolites, as well as the much more complex mechanisms involved for Ti-zeolites.…”
Section: Selective Catalytic Oxidation Of Ammonia (Nh 3 -Sco)mentioning
confidence: 89%
“…Therefore, aggregation of such copper species under calcination conditions is much easier for Ti-zeolites than Al-zeolites. The study byŚwięs et al [9] showed the better activity of the copper-modified layered titanium-silicon zeolites at lower temperatures compared to catalysts based on Alzeolites (Figure 7). This effect was more evident for the Cu-Ti-FER and Cu-Al-FER catalysts than for their delaminated analogous counterparts (Figure 7).…”
Section: Selective Catalytic Oxidation Of Ammonia (Nh 3 -Sco)mentioning
confidence: 93%
See 3 more Smart Citations